Multiple Targets of Salicylic Acid and Its Derivatives in Plants and Animals - Klessig, Daniel F.; Tian, Miaoying; Choi, Hyong Woo (Frontiers in Immunology, 2016)
Salicylic acid (SA) is a critical plant hormone that is involved in many processes, including seed germination, root initiation, stomatal closure, floral induction, thermogenesis, and response to abiotic and biotic stresses. Its central role in plant immunity, although extensively studied, is still only partially understood. Classical biochemical approaches and, more recently, genome-wide high-throughput screens have identified more than two dozen plant SA-binding proteins (SABPs), as well as multiple candidates that have yet to be characterized. Some of these proteins bind SA with high affinity, while the affinity others exhibit is low. Given that SA levels vary greatly even within a particular plant species depending on subcellular location, tissue type, developmental stage, and with respect to both time and location after an environmental stimulus such as infection, the presence of SABPs exhibiting a wide range of affinities for SA may provide great flexibility and multiple mechanisms through which SA can act. SA and its derivatives, both natural and synthetic, also have multiple targets in animals/humans. Interestingly, many of these proteins, like their plant counterparts, are associated with immunity or disease development. Two recently identified SABPs, High Mobility Group Box protein (HMGB) and Glyceraldehyde 3-Phosphate Dehydrogenase (GAPDH), are critical proteins that not only serve key structural or metabolic functions, but also play prominent roles in disease responses in both kingdoms.